Towards a better understanding of work participation among employees with common mental health problems: a systematic realist review - Suzanne GM van Hees; Bouwine E Carlier; Emma Vossen; Roland WB Blonk; Shirley Oomens (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVES: Common mental health problems (CMHP) represent a major health issue and burden to employees and employers. Under certain conditions work contributes to wellbeing and participation of employees with CMHP. Promoting work participation is important, however the specific conditions in which work participation occurs is complex and largely unclear. This calls for a novel, realistic approach to unravel the complex relationship between outcomes, context and underlying mechanisms of work participation. METHODS: In the present realist review, peer-reviewed studies conducted between 1995 and 2020 were systematically reviewed on the outcome measures `stay at work` (SAW) and `work performance` (WP). The database search from seven databases identified 2235 records, of which 61 studies met the selection criteria and methodological rigor. RESULTS: The synthesis demonstrates how work participation is promoted by the following mechanisms and contextual factors: (i) organizational climate and leadership, (ii) social support, (iii) perceived job characteristics, (iv) coping styles, (v) health symptoms and severity, (vi) personal characteristics, and (vii) features of interventions. An explanatory framework, based on the Capability-for-Work model, presents a new set of capabilities leading to SAW and WP. CONCLUSIONS: This systematic realist review revealed mechanisms and contextual factors that promote both SAW and WP among employees with CMHP. These show how the organizational climate, social support in the work context, job characteristics and certain capabilities enable employees with CMHP to participate at work. Our contributions and practical implications are discussed, providing valuable insights for employers, professionals and researchers in the development of evidence-based interventions.